2019
DOI: 10.3390/jcm8101609
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific miRNAs Regulate the Development of Thoracic Aortic Aneurysm: The Emerging Role of KLF4 Network

Abstract: MicroRNAs (miRNAs) are critical regulators of the functional pathways involved in the pathogenesis of cardiovascular diseases. Understanding of the disease-associated alterations in tissue and plasma will elucidate the roles of miRNA in modulation of gene expression throughout development of sporadic non-syndromic ascending thoracic aortic aneurysm (TAA). This will allow one to propose relevant biomarkers for diagnosis or new therapeutic targets for the treatment. The high-throughput sequencing revealed 20 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
(70 reference statements)
0
22
1
Order By: Relevance
“…The hypothesis of the assessment of potential diabetes/cardiovascular risk in children prenatally exposed to GDM was based on the knowledge that a serious of microRNAs play a role in the pathogenesis of diabetes mellitus and cardiovascular/cerebrovascular diseases ( Table 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , <...>…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis of the assessment of potential diabetes/cardiovascular risk in children prenatally exposed to GDM was based on the knowledge that a serious of microRNAs play a role in the pathogenesis of diabetes mellitus and cardiovascular/cerebrovascular diseases ( Table 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , <...>…”
Section: Discussionmentioning
confidence: 99%
“…Previously, by searching the Medline database we identified a large scale of microRNAs playing a role in pathogenesis of diabetes mellitus and cardiovascular/cerebrovascular diseases. Finally, we selected for the study a shortlist of 29 microRNAs demonstrated repetitively by numerous scientific teams to be associated with normal stages (development and homeostasis of the cardiovascular system, angiogenesis, and adipogenesis) and pathological conditions and diseases (vascular endothelial dysfunction and inflammation, hypoxia, hypertension and regulation of hypertension-related genes, obesity, dyslipidaemia, atherosclerosis and atherosclerotic plaque formation, insulin resistance, diabetes mellitus and diabetes-related complications, metabolic syndrome, cardiovascular diseases involving the blood vessels (coronary and peripheral artery diseases, carotid artery disease, pulmonary arterial hypertension, cerebrovascular disease, aortic and intracranial aneurysms), cardiovascular diseases involving the heart (congenital heart disease, cardiomyopathies, cardiac dysrhythmias, hypertensive heart disease, myocardial disease, valvular heart disease, inflammatory heart disease, rheumatic heart disease, pulmonary heart disease, and heart failure), chronic kidney disease, ischemia/reperfusion injury, cardiac regeneration and cachexia) ( Table 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ,…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs participate in various cell processes by targeting several genes that participate in a wide range of cell signaling pathways. More specifically, a single miRNA may affect expression of several target genes and may induce changes in various processes and pathways presenting additional mechanisms by which a disease may be induced [68,69]. Therefore, miRNAs are involved in many pathological processes that are present in different diseases and they may show a cell-specific regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, an miRNA microarray assay identified miR-574-5p as a biomarker that was successfully able to differentiate between TAA patients and controls in a small cohort [136]. Another study used high-throughput miRNA sequencing on a small cohort of TAA patients and found two plasma miRNAs, miR-122-3p and miR-483-3p, that also showed sufficient discrimination for use as a biomarker [137]. Interestingly, the same study found striking sex-related differences in miRNA profiles with more dysfunction noted in males and noted that Krüppel-like factor 4 (KLF4), an important regulator of vascular SMCs, had significantly increased expression in TAA patients [137].…”
Section: Genetic Testing-past and Futurementioning
confidence: 99%
“…Another study used high-throughput miRNA sequencing on a small cohort of TAA patients and found two plasma miRNAs, miR-122-3p and miR-483-3p, that also showed sufficient discrimination for use as a biomarker [137]. Interestingly, the same study found striking sex-related differences in miRNA profiles with more dysfunction noted in males and noted that Krüppel-like factor 4 (KLF4), an important regulator of vascular SMCs, had significantly increased expression in TAA patients [137]. Both studies show how miRNA biomarkers, if validated in a clinical setting, could be a useful for detection of TAAD.…”
Section: Genetic Testing-past and Futurementioning
confidence: 99%